Limitations of glycated albumin standardization when applied to the assessment of diabetes patients - Lenters-Westra, Erna; Atkin, Stephen L.; Kilpatrick, Eric S.; Slingerland, Robbert J.; Sato, Asako; English, Emma (Clinical Chemistry and Laboratory Medicine (CCLM), 2024)
Glycated albumin (GA) has potential value in the management of people with diabetes; however, to draw meaningful conclusions between clinical studies it is important that the GA values are comparable. This study investigates the standardization of the Norudia Glycated Albumin and Lucica Glycated Albumin-L methods. The manufacturer reported imprecision was verified by performing CLSI-EP15-A3 protocol using manufacturer produced controls. The Japanese Clinical Chemistry Reference Material (JCCRM)611-1 was measured 20 times to evaluate the accuracy of both methods. GA was also measured in 1,167 patient samples and results were compared between the methods in mmol/mol and %. Maximum CV for Lucica was ≤0.6 % and for Norudia ≤1.8 % for control material. Results in mmol/mol and % of the JCCRM611-1 were within the uncertainty of the assigned values for both methods. In patient samples the relative difference in mmol/mol between the two methods ranged from -10.4 % at a GA value of 183 mmol/mol to +8.7 % at a GA value of 538 mmol/mol. However, the relative difference expressed in percentage units ranged from of 0 % at a GA value of 9.9 % to +1.7 % at a GA value of 30 %. The results in mmol/mol between the two methods for the patient samples were significantly different compared to the results in %. It is not clear why patient samples behave differently compared to JCCRM611-1 material. Valuable lessons can be learnt from comparing the standardization process of GA with that of HbA .